STUDI KEMASYARAKATAN PENANGANAN KORBAN BENCANA BANJIR DAN TANAH LONGSOR DI JEMBER 2006 - Soedarso Soedarso (Institut Teknologi Sepuluh Nopember, 2008)
This article is the report of the research result. The research aims to know how strategy of adaptation was carried out by the victim of disaster of torrent and landslide in Jember, early January 2006. The research methodology used are observation and non-structured interview under researcher guidance. The data taken in July 2007 where the disaster takes place, that is in Subdistrict Panti, Jember.A period of emergency, safe disaster victims live in the evacuation tents during 6 month, before they are evacuated in the aid house which have been built by local government. Housing is built under hilly area in which another disaster can emerge, therefore, it requires further attention. A period of recovery still continues until now. The victims have not been able to forget yet about what happens to them. They are still trauma of losing anything, and importantly of feeling scare. They remain expect attention and assistance from the government and related parties.